DEFINING SEMANTIC LEVELS OF DETAIL FOR INDOOR MAPS - J. Chen (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2018)
One major challenge in creating indoor maps involves defining their levels of detail or LODs. While a consensus has emerged that indoor maps have at least two types of LODs, semantic and geometric, questions remain regarding their nature, their partitioning, and their relationships with each other as well as with other forms of LOD. Since semantics deals with the meanings of things, semantic LODs (SLODs) deal with the definition, classification, and partitioning of mapped entities. Unlike geometric LODs that are amenable to automation, SLODs have a more qualitative nature that defies automation and requires the careful application of human judgment. This paper proposes a framework for organizing semantic LODs by first classifying them based on the tangibility of mapped entities (i.e., intangible open spaces versus tangible physical features comprised of building structures and equipment and furnishings) and then partitioning each class based on the idea of permanence, defined here as an entity’s tendency to remain stationary over time. A cartographic process for integrating SLODs with geometric and appearance LODs is also introduced along with several examples.